Persistent socioeconomic disparities in cardiovascular risk factors and health in the United States: Medical Expenditure Panel Survey 2002–2013. (February 2018) - Valero-Elizondo, Javier; Hong, Jonathan C.; Spatz, Erica S.; Salami, Joseph A.; Desai, Nihar R.; Rana, Jamal S.; Khera, Rohan; Virani, Salim S.; Blankstein, Ron; Blaha, Michael J.; Nasir, Khurram
Abstract: Background and aims: Socioeconomic status (SES) has been linked to worse cardiovascular risk factor (CRF) profiles and higher rates of cardiovascular disease (CVD), with an especially high burden of disease for low-income groups. We aimed to describe the trends in prevalence of CRFs among US adults by SES from 2002 to 2013. Methods: Data from the Medical Expenditure Panel Survey was analyzed. CRFs (obesity, diabetes, hypertension, physical inactivity, smoking and hypercholesterolemia), were ascertained by ICD-9-CM and/or self-report. Results: The proportion of individuals with obesity, diabetes and hypertension increased overall, with low-income groups representing a higher prevalence for each CRF. Of note, physical inactivity had the highest prevalence increase, with the "lowest-income" group observing a relative percent increase of 71.1%. Conclusions: Disparities in CRF burden continue to increase, across SES groups. Strategies to potentially eliminate the persistent health disparities gap may include a shift to greater coverage for prevention, and efforts to engage in healthy lifestyle behaviors.